Antenatal Compliance Relationship Care with Anxiety of Pregnant Women in Time Pandemic Covid-19 - Sitti Fatimah; Musni Musni; A. Ulfa Fatmasanti; Kiki Reski Rahmadani (Journal La Medihealtico, 2022)
Pregnant women, who are at a higher risk of getting the coronavirus than other populations, have felt the psychological effects of the COVID-19 pandemic. Avoiding antenatal care (ANC) appointments due to anxiety puts the mother and fetus at risk for complications like undiagnosed bleeding at any point in the pregnancy. The purpose of this study is to examine whether or not pregnant women's fear about the Covid 19 epidemic affects their likelihood of keeping up with their scheduled ANC checkups. Analytical approaches based on cross-sectional studies. During April and May of 2021, investigators visited the Sibulue Health Center in Bone Regency. The demographic requirements are met by the responses of 48 pregnant women in their second and third trimesters who are able to explain their sentiments and anxieties. Twenty-eight pregnant women (58.3%) and nine pregnant women (18.0%) who did not suffer anxiety made frequent ANC visits to healthcare facilities throughout the Covid-19 epidemic. Among pregnant women, 18 (37.5%) had anxiety and were not attending ANC on a regular basis. Nine pregnant women (n = 9) did not report experiencing any anxiety, however two of them did not obtain consistent ANC. Using a chi-square test, we found a significance level of 0.001. (p 0.05). Women's worry during pregnancy was associated with their use of prenatal care services during the Covid-19 pandemic.